Body Mass Index of Adult Special Olympians by Country Economic Status. Issue 4 (2nd September 2015) - Temple, Viviene A.; Foley, John T.; Lloyd, Meghann
Abstract: Many low‐ and middle‐income countries have experienced an epidemic of obesity in the last few decades. However, no studies have examined the relationship between country economic status and weight status among adults with ID. This study compared the prevalence of underweight, normal weight, overweight, and obesity among adult Special Olympics participants by country economic status. A total of 19, 295 (men, n = 12, 037) measured height and weight records were available from the Special Olympics International (SOI) Health Promotion database. The 159 countries in the database were recoded according to the World Bank's classification of country economic status as: low‐income, lower middle‐income, upper middle‐income, and high‐income. Body mass index (BMI; kg/m 2 ) prevalence rates were calculated for underweight, normal weight, overweight, and obesity for men and women by economic status. Odds ratios, adjusted for age and sex, were used to examine differences in BMI by country economic status. Overall, 31.9% of SOI participants from low‐income economies, 48.6% from lower middle‐income, 43.6% from upper middle‐income, and 66.0% from high‐income economies had BMI indices outside of the normal range. For the low‐income countries, the proportion of underweight and overweight/obesity was similar (17.2% and 14.7%, respectively). For the other three levels of economy, participants with BMI levels outside the normal range were largely overweight/obese, rather than underweight. Women, older participants, and those from higher‐income countries were much more likely to be overweight/obese. Considerably, more research on the key behaviors associated with BMI status and the extent to which environments (economic, social, and physical) are obesogenic is needed to explain these differences and to begin to design interventions that can be both targeted for persons with ID and coherently implemented across sectors and settings.